Public IP Efficiency and Data Center Security Enhancement with Reverse Proxy Implementation - Achmad Sandy Bukhari; Mohammad Iqbal (Ikatan Ahli Informatika Indonesia Nusantara, 2024)
With the increasing frequency of cyber-attacks, the trend of national cybersecurity traffic anomalies reached 976,429,996 incidents in 2022. Additionally, the world is now facing the fact that the supply of Public IPv4 addresses available for allocation is diminishing. IPv4 uses 32-bit addressing, which provides only over 4 billion unique IP addresses. By conducting research using two methods, namely a server without a reverse proxy and a server with an applied reverse proxy, it was found that implementing NGINX with a reverse proxy can lead to savings in public IPv4 addresses. Regardless of the number of servers, only one public IPv4 address is needed, which reduces the number of IPs required and also prevents cyber-attacks on the server. Testing with DNSChecker and whatismyipaddress showed that after applying the reverse proxy with NGINX, the application server could not be identified or accessed by external parties. Only the reverse proxy server was accessible to outsiders. As the number of applications increases, which directly correlates with the need for public IPv4 addresses, the study's results show that applying a reverse proxy with NGINX in a data center can overcome the limitations of public IPv4 addresses. As the number of virtual machines and applications grows, a single public IPv4 address applied to the reverse proxy server suffices. Thus, implementing a reverse proxy with NGINX allows multiple servers to use just one public IPv4 address.